Social participation in the health technology incorporation process into Unified Health System - Silva, Aline Silveira; Sousa, Maria Sharmila Alina de; Silva, Emília Vitória da; Galato, Dayani (Revista de Saúde Pública, 2019)
OBJECTIVE: To describe the current process of social participation in the incorporation of health technologies in Brazil, within the context of the Unified Health System (SUS). METHODS: A descriptive study was conducted based on the analysis of official records of the actions of the National Committee for Health Technology Incorporation into Unified Health System and its website, from the beginning of its activities in January 2012 until December 2017. RESULTS: The findings indicate that, in Brazil, there are legal instruments related to social participation in health, including the health technology assessment (HTA) field. However, its implementation is relatively recent and has been carried out gradually. In addition to the legal instruments (National Health Council representative, public consultation and public hearing forecast), other information and transparency strategies have been shown to be allied to social participation in the incorporation of health technologies. However, activities such as legally provided public hearings have not yet been carried out. CONCLUSIONS: Several actions to foster social participation were developed over the analyzed period, but they need to be evaluated in order to maintain or improve them. In addition, there is a need for more qualified social participation in the various existing spaces, including those prescribed by law.